Numerical simulation of head-on collision dynamics of binary droplets with various diameter ratios by the two-phase lattice kinetic scheme. (30th May 2018) - Yoshino, Masato; Sawada, Jumpei; Suzuki, Kosuke
Highlights: Binary droplet collisions for various diameter ratios (Δ) are simulated. The critical Weber number (Wec ) between coalescence and separation is investigated. We c reaches its minimum at Δ = 0.7 . Relation between Wec and Δ is independent of the Reynolds number (Re) for Re>2000. Energy plays a vital role in after-collision patterns as well as Wec . Abstract: Collision dynamics of binary droplets with various diameter ratios is simulated by the two-phase lattice kinetic scheme. We investigate the effects of the Weber number We, the Reynolds number Re, which are based on the properties of the smaller liquid droplet, and the diameter ratio of the droplets Δ on the collision behavior. These dimensionless parameters are varied in the range of 10 ≤ We ≤ 100, 100 ≤ Re ≤ 4000, and 0.4 ≤ Δ ≤ 1.0. We first simulate binary collisions of equal-size droplets in order to confirm the validity of the method. The calculated shape and the size of the droplets are in good agreement with results by other studies. We next calculate binary collisions of unequal-size droplets, and find that the behavior of the droplets after collision is classified into coalescence and separation. In addition, the critical Weber number between coalescence and separation is calculated for various diameter ratios and Reynolds numbers. It is found from these results that the critical Weber number becomes minimum when the diameter ratio is around 0.7 independently of the Reynolds number. Also, the collision dynamics at the critical state is further investigated and discussed in terms of relative viscous dissipation.